1908 Ill. Laws 40-41 - (:unkn) unknown (My University, 1908)
Regulate Storage of Combustibles--Fireworks, §1334, pt. 65: Amended the powers granted to cities with a population of one hundred thousand or more to regulate and prevent the storage of gunpowder, tar, pitch, resin, coal oil, benzine, turpentine, hemp, cotton, nitro-glycerine, petroleum, or other combustible or explosive material.
Keywords: GUNPOWDER - STORAGE